PENGABDIAN KEPADA MASYARAKAT PELATIHAN PEMANFAATAN WEBSITE DESA DAN INTERNET DASAR PADA PEKON BUMI AYU KECAMATAN PAGELARAN (LP3K Lampung, 2022)
Internet technology which has now become a demand for life must be used optimally. Progress if the government began to adopt the technology as the main infrastructure of public services. In the following article, we try to describe how serious the government is in working on an e-government system in public services. State service to its citizens is a mandate stated in the 1945 Constitution and clarified again in Law no. 25 of 2009 concerning Public Services. The Law on Public Services regulates the principles of good governance so that government functions can run effectively. Public services are carried out by government agencies or corporations to strengthen democracy and human rights, promote economic prosperity, and social cohesion, reduce poverty, increase environmental protection, be wise in the use of natural resources, and deepen trust in government and public administration.